Ocorrência de tuberculose em um hospital psiquiátrico do interior de Goiás - Da Costa, Hindenburg Cruvinel Guimarães [UNESP]; Malaspina, Ana Carolina [UNESP]; De Mello, Fernando Augusto Fiúza; Leite, Clarice Queico Fujimura [UNESP] (FapUNIFESP (SciELO), 2006)
Objective: To investigate the prevalence of infection, disease and eventual institutional outbreak of tuberculosis in a psychiatric hospital using the PPD test, as well as testing for mycobacteria in material collected from the respiratory tree and using molecular tracking technique based on insertion sequence 6110 (IS6110). Methods: Between February and August of 2002, PPD tests were given to 74 inpatients and 31 staff members at a psychiatric hospital in the city of Rio Verde, located in the state of Goiás, Brazil. In addition, respiratory tree material collected from the inpatients was submitted to testing for Mycobacterium tuberculosis. Results: Among the patients analyzed, mycobacteria were isolated from five (6.8%): four identified as M. tuberculosis and one as M. chelonae. The M. tuberculosis isolates were sensitive to isoniazid and rifampicin, and, when submitted to the restriction fragment length polymorphism/IS6110 technique, presented unique genetic profiles, totally distinct from one another, suggesting that all of the tuberculosis cases were due to endogenous reactivation. It was not possible to characterize this group of cases as an institutional outbreak. Performing the two-step tuberculin test in the patients, the infection rates were 23% and 31%, compared with 42% among staff members, who were submitted to the one-step test. Conclusion: The results indicate a high incidence of tuberculosis infection among inpatients and hospital staff, as well as a high occurrence of the disease among inpatients.
Tuberculosis in a psychiatric hospital in the state of Goiás, Brazil
Keywords: Hospitals, psychiatric; Mycobacterium chelonae; Mycobacterium tuberculosis; Tuberculin test; Tuberculosis/epidemiology; bacterial DNA; adult; Brazil; disease transmission; DNA fingerprinting; female; genetics; hospital personnel; human; isolation and purification; lung tuberculosis; male; mental hospital; middle aged; prevalence; restriction fragment length polymorphism; statistics; Adult; DNA Fingerprinting; DNA, Bacterial; Female; Hospitals, Psychiatric; Humans; Male; Middle Aged; Personnel, Hospital; Polymorphism, Restriction Fragment Length; Prevalence; Tuberculosis, Pulmonary